If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (t + 4)(t + 25) = 0 Reorder the terms: (4 + t)(t + 25) = 0 Reorder the terms: (4 + t)(25 + t) = 0 Multiply (4 + t) * (25 + t) (4(25 + t) + t(25 + t)) = 0 ((25 * 4 + t * 4) + t(25 + t)) = 0 ((100 + 4t) + t(25 + t)) = 0 (100 + 4t + (25 * t + t * t)) = 0 (100 + 4t + (25t + t2)) = 0 Combine like terms: 4t + 25t = 29t (100 + 29t + t2) = 0 Solving 100 + 29t + t2 = 0 Solving for variable 't'. Factor a trinomial. (25 + t)(4 + t) = 0Subproblem 1
Set the factor '(25 + t)' equal to zero and attempt to solve: Simplifying 25 + t = 0 Solving 25 + t = 0 Move all terms containing t to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + t = 0 + -25 Combine like terms: 25 + -25 = 0 0 + t = 0 + -25 t = 0 + -25 Combine like terms: 0 + -25 = -25 t = -25 Simplifying t = -25Subproblem 2
Set the factor '(4 + t)' equal to zero and attempt to solve: Simplifying 4 + t = 0 Solving 4 + t = 0 Move all terms containing t to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + t = 0 + -4 Combine like terms: 4 + -4 = 0 0 + t = 0 + -4 t = 0 + -4 Combine like terms: 0 + -4 = -4 t = -4 Simplifying t = -4Solution
t = {-25, -4}
| 2z+8z=180 | | 3x+y-4-7y=12 | | n/4+3=14 | | 3x^2y+39xy-87y=0 | | 10x-32=5m+-23 | | f(x)=4+y | | 7+5(2-6)= | | 1/7x=1/3 | | -20+n=10 | | 27a-5=-2+15c | | c^2-c-36=0 | | -d^2+14d-45=0 | | 59.85+(29.95*6)=x | | 9-y=-4y+23 | | 12-4(2)+8/2 | | 7+5(2+6)= | | x/3-x/8=6 | | 6y-7=4y-1 | | -4+n=-2 | | 13x=-13 | | 2n+3n+7=-14 | | 6-7=4y-1 | | 8k=24+2k | | 1/4(8y-12)= | | -3g+3=-8g+7g | | 40+(19.95*9)=x | | -6n=3 | | q^2-21q+20=0 | | 3=6m-3m-2 | | 0.21y-0.4=0.11y+2-0.7y | | 2w+3=3w-1 | | 3x-9=-15 |